2014
DOI: 10.1080/09670262.2014.976662
|View full text |Cite
|
Sign up to set email alerts
|

Ulva flexuosa(Ulvaceae, Chlorophyta) inhabiting inland aquatic ecosystems: molecular, morphological and ecological discrimination of subspecies

Abstract: Species of Ulva (Ulvaceae, Chlorophyta) are relatively common macroalgae in most coastal areas. In this paper, we examine Ulva in inland aquatic ecosystems to determine relationships between the chemical parameters of the water and the Ulva taxa present. Two groups of samples of freshwater Ulva were selected from: (i) habitats with high salinity levels, and (ii) habitats with fresh or slightly saline waters. We showed that these two groups of Ulva, which occupy distinct habitats, represent two separate taxa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…paradoxa population occurs in a high-mineral-concentration (van der Aa 2003), chloride sodium sulphate, low-nitrate (due to biological consumption? ), oligo-mesotrophic (Dodds et al 1998) spring habitat (Table 1), in partial agreement with previous reports of the taxon in other parts of the world (Rybak et al 2014). Cyanobacterial taxa identified in Ain Abu Sherouf, such as Oscillatoria limosa and Phormidium tergestinum, suggest a relatively "polluted" (nutrient-rich) status (Komárek & Anagnostidis 2005).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…paradoxa population occurs in a high-mineral-concentration (van der Aa 2003), chloride sodium sulphate, low-nitrate (due to biological consumption? ), oligo-mesotrophic (Dodds et al 1998) spring habitat (Table 1), in partial agreement with previous reports of the taxon in other parts of the world (Rybak et al 2014). Cyanobacterial taxa identified in Ain Abu Sherouf, such as Oscillatoria limosa and Phormidium tergestinum, suggest a relatively "polluted" (nutrient-rich) status (Komárek & Anagnostidis 2005).…”
Section: Discussionsupporting
confidence: 90%
“…In their recent contribution, Rybak et al (2014) reported samples of subsp. paradoxa with a comparable (although in average still larger) width of 50-400 µm, suggesting that very narrow filiform thalli may be in fact relatively common in this taxon (see Table S1 for more details).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seasonal collections of Ulva thalli were made at one location in the stream, and the species were identified using the ITS2 rDNA region and rbcL gene sequences, which were previously described by Rybak et al (2014). All specimens belonged to one species of green algae, Ulva flexuosa.…”
Section: Methodsmentioning
confidence: 99%